2009
DOI: 10.1007/s10546-009-9407-1
|View full text |Cite
|
Sign up to set email alerts
|

Stratiform Cloud—Inversion Characterization During the Arctic Melt Season

Abstract: Data collected during July and August from the Arctic Ocean Experiment 2001 illustrated a common occurrence of specific-humidity (q) inversions, where moisture increases with height, coinciding with temperature inversions in the central Arctic boundary layer and lower troposphere. Low-level stratiform clouds and their relationship to temperature inversions are examined using radiosonde data and data from a suite of remote sensing instrumentation. Two low-level cloud regimes are identified: the canonical case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 39 publications
8
85
0
Order By: Relevance
“…Seasonal variation in temperature inversion occurrence is very similar to its humidity inversion counterparts, and the temperature inversion frequency of occurrence above an AMC is about 8 times as high as that below an AMC (Figures 7a and 7b). This result agrees well with previous studies, where specific humidity inversions occurred coincidently with temperature inversions over the Arctic [Sedlar and Tjernström, 2009]. The strong inversion occurrences for both humidity and temperature above an AMC provide the moisture sources from above for the formation and maintenance of AMCs.…”
Section: 1002/2014jd023022supporting
confidence: 93%
“…Seasonal variation in temperature inversion occurrence is very similar to its humidity inversion counterparts, and the temperature inversion frequency of occurrence above an AMC is about 8 times as high as that below an AMC (Figures 7a and 7b). This result agrees well with previous studies, where specific humidity inversions occurred coincidently with temperature inversions over the Arctic [Sedlar and Tjernström, 2009]. The strong inversion occurrences for both humidity and temperature above an AMC provide the moisture sources from above for the formation and maintenance of AMCs.…”
Section: 1002/2014jd023022supporting
confidence: 93%
“…Sedlar and Tjernström (2009), Solomon et al (2011) and Sedlar et al (2012) found, however, that inversions of temperature and humidity typically coincide near the cloud top. A potential explanation for the different results is that the abovementioned studies mostly addressed the ice-covered Arctic Ocean, whereas the IGRA data set is more representative of the pan-Arctic land areas.…”
Section: Discussionmentioning
confidence: 98%
“…Entrainment also becomes a source of boundary-layer moisture. Cloud tops penetrating into the lower inversion have been found to be a dominating feature in many Arctic observations, for example from cloud radar and temperature profiles from AOE-2001, ASCOS, SHEBA and at Barrow, Alaska, (Sedlar and Tjernström, 2009;Sedlar et al, 2012) and have been suggested as important for the persistence of Arctic mixed-phase stratocumulus clouds (Solomon et al, 2011).…”
Section: Vertical Structurementioning
confidence: 99%